2021
DOI: 10.1155/2021/5558694
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Skin Cancer Knowledge, Sun Exposure, and Tanning Behavior among University Students: Investigation of an Opportunity Sample of German University Students

Abstract: Ultraviolet radiation (UVR) is the most important risk factor for developing skin cancer. University students can be considered as a particularly high-risk group for long- and short-term adverse effects of UVR due to intensive solar UVR exposure and high rates of sunburn. While validated questionnaires for assessing solar UVR exposure and sun protection behavior are available in German, a questionnaire for assessing the level of knowledge about this topic is still missing. We conducted a literature search for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 69 publications
0
10
0
7
Order By: Relevance
“…66.9% of respondents did not prefer sitting in the winter sun for long periods of times. Table (7) shows data on sunscreen knowledge and use among our respondents. 42.6% reported that >30 SPF sunscreen was enough for sun protection in the summer and 61.7% believed apply sunscreen on face only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…66.9% of respondents did not prefer sitting in the winter sun for long periods of times. Table (7) shows data on sunscreen knowledge and use among our respondents. 42.6% reported that >30 SPF sunscreen was enough for sun protection in the summer and 61.7% believed apply sunscreen on face only.…”
Section: Resultsmentioning
confidence: 99%
“…one including eight questions appraising sun habits and sun protection behavior, and one including five questions assessing readiness to increase sun protection. The contents of the two sections were developed from previous studies [7]. Part I mapping sun exposure/protection habits, includes eight questions based on five-grade Likert scale scores (0-4 points), resulting in a total score of 0-32 points, reflecting an increasing risk exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Data concerning the items' reliability was not available in the original publication or the German pilot study. 25,31 We found it necessary to deviate from the original in two details, which should be noted when comparing SCSK scores across studies in the future. As a first and content-wise negligible change, the correct answer to item 13 is "true" in order to avoid a double negative in the translation.…”
Section: Sun Protection Knowledge (Scsk)mentioning
confidence: 99%
“…32 Recently, the SCSK has been translated and pilot tested with a sample of students of vocational education teaching. 25…”
Section: Questionnairesmentioning
confidence: 99%
“…32 Kürzlich wurde die SCSK übersetzt und in einer Pilotstudie mit einer Stichprobe aus Berufsschülern getestet. 25…”
Section: Fragebögenunclassified